2019
DOI: 10.12669/pjms.35.4.286
|View full text |Cite
|
Sign up to set email alerts
|

Electrolyte imbalance in critically ill paediatric patients

Abstract: Objective: To determine the frequency and outcome of electrolyte imbalance in seriously ill children admitted in Paediatric Intensive Care Unit (PICU) of a public sector hospital in Karachi. Methods: All children between the ages of one month to 12 years admitted in PICU from May 2017 to October 2017 were included. Blood samples were drawn to determine the baseline sodium, potassium, calcium, magnesium and phosphorous and followed 24 hourly or earlier, if needed (Those who had imbalance at admission or o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 14 publications
2
26
1
1
Order By: Relevance
“…In this study, we detected that hyperkalemia was the second most common serum electrolyte abnormality next to hyponatremia (27.5%). Previous studies have reported the incidence of hyperkalemia as 26.8%, 26.6%, 24.8%, 14%, 18.8%, 15.3% (4,6,(13)(14)(15)18). In our study, the most common underlying disease of those with hyperkalemia was asthma/acute bronchiolitis.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…In this study, we detected that hyperkalemia was the second most common serum electrolyte abnormality next to hyponatremia (27.5%). Previous studies have reported the incidence of hyperkalemia as 26.8%, 26.6%, 24.8%, 14%, 18.8%, 15.3% (4,6,(13)(14)(15)18). In our study, the most common underlying disease of those with hyperkalemia was asthma/acute bronchiolitis.…”
Section: Discussionsupporting
confidence: 54%
“…The most common underlying disease in these cases was acute gastroenteritis. In different studies this incidence was reported 64%, 57.4%, 49%, 28%, 30.58%, 9.6% (4,6,(13)(14)(15)18) .The incidence of hypokalemia was higher than our results in all studies except Rothrock et al (13).…”
Section: Table Iii: Demographiccontrasting
confidence: 52%
See 1 more Smart Citation
“…within 48 hours of admission, was reported in 14 cases of which 12 had electrolyte disturbances. 27 .…”
Section: Discussionmentioning
confidence: 99%
“…(Table 6). 11,12 Hypokalemia is serum potassium concentration below 3.5 mEq/l.9 It occurs in about 15% children admitted to PICU. 13 Figure 2 shows that in this study distribution of electrolyte abnormalities were Hyponatremia (10.59%), Hypernatremia (4.70%), Hypokalemia (3.82%), Hyperkalemia (16.18%) being highest, Hypocalcemia (2.62%).…”
Section: Resultsmentioning
confidence: 99%